Hemodynamic and Morphological Parameters of Ruptured Mirror Posterior Communicating Artery Aneurysms - Yuan, Jinlong; Huang, Chenlei; Li, Zhenbao; Jiang, Xiaochun; Zhao, Xintong; Wu, Degang; Lai, Nianshen; Liu, Jiaqiang; Zhang, Bingbing; Qin, Feiyun; Xia, Dayong; Fang, Xinggen (Frontiers in Neurology, 2021)
Objective: Morphological and hemodynamic parameters might predict rupture of intracranial aneurysms (IAs). A practical model for the study is patients with ruptured mirror IAs in which one ruptured, and the other unruptured. Although there have been analyses of the morphological and hemodynamic of ruptured mirror posterior communicating artery aneurysms (PComAAs), the sample sizes in these studies were small and only considered hemodynamics or morphological characters. Therefore, this study aimed to investigate the morphological and hemodynamic parameters associated with ruptured mirror PComAAs. Methods: We considered 72 patients with ruptured mirror PComAAs using computational fluid dynamics (CFD). Ruptured mirror PComAAs were divided into ruptured and unruptured groups. 14 morphological and 8 hemodynamic parameters were calculated and compared. Significant parameters were analyzed by the multivariate logistic regression to identify independent risk factors. Receiver operating characteristics (ROC) analysis was performed, and the area under the ROC curve (AUC) was calculated for all independent risk factors to determine the predictability and identify the optimal threshold. Results: Four hemodynamic and three morphological parameters were significantly different between ruptured and unruptured groups:normalized wall shear stress (NWSS), mean WSS, low wall shear WSS area (LSA%), size, aspect ratio (AR), size ratio (SR) and inflow angle (IA). Multivariate logistic regression analysis showed that AR, SR, NWSS, mean WSS, and LSA% were all independent factors significantly associated with PComAAs rupture. The ROC analysis for independent risk factors indicated that AR (0.751), NWSS (0.755), mean WSS (0.69), and LSA (0.778) had merely acceptable AUC values. Only SR (0.803) had a high acceptable AUC value. The threshold value of SR was 1.96. CONCLUSIONS: SR (>1.96) was the most significant parameter associated with IAs rupture, whereas AR, NWSS, mean WSS, LSA were independently characterized the status of IAs rupture.